Separatism in South Cameroon: Sources and Prospects - T. S. Denisova (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2021)
In the 2010s, the issue of separatism in Africa gained special significance in connection with the emergence in 2011 of a new state – the Republic of South Sudan (RSS), where a military and political conflict has continued throughout the entire period of independent development, accompanied by massive casualties among the civilian population. The situation in the RSS underscores the weakness of secessionism as a tool for solving the problems of national identity, socio-economic development and political marginalization, and also raises the question of whether separatism in Africa is able to lead to stability, an improvement in living standards and an increase in the level of security of citizens of breakaway territories. The present paper examines the historical background of separatism in South Cameroon and of organizations and armed groups fighting for the separation of the region from the Republic of Cameroon and for the independence of the self-declared Republic of Ambazonia. Currently, the country is engulfed in a military and political conflict, the parties to which are the central (Francophone) government and the Anglophone secessionist movements, which include dozens of armed groups with varying goals and interests and which fight among themselves for influence on local communities, resources, and the right to represent Cameroon’s Anglophone minority in the international arena. In fact, South Cameroon is now in a state of war of all against all. The situation in South Cameroon is compounded by the fact that President Paul Biya’s government simultaneously has to fend off attacks by Boko Haram terrorists in the far north of the country and deal with a socio-economic crisis, which is accompanied by rising unemployment, which, in turn, allows insurgents to expand their ranks with relative ease. The authors note, however, that the separatists do not enjoy the support of the world community and, unlike many other African rebel movements, receive hardly any financial or military-technical assistance from outside, which dooms their armed struggle and increases the consequence of a peaceful agreement with the government.